Clinical presentation, diagnosis and treatment of intrahepatic cholestasis of pregnancy - Yu. B. Uspenskaya; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the lecture. To present the modern concept of etiology and pathogenesis of the intrahepatic cholestasis of pregnancy (ICP) and the modern diagnostic and treatment approaches to gastroenterologists. Summary. The etiology and pathogenesis of ICP are related to disorders of bile acid metabolism caused by hormonal factors (elevation of estrogen and progesterone levels) and genetic predisposition. The leading clinical signs of ICP include pruritus and jaundice that develop most commonly in the third trimester of pregnancy, and characteristic changes of laboratory scores: increase in bile acid level (over 10 mcmol/l) and moderate elevation of transaminase activity. Severity of ICP and complication risk for mother and fetus correlate to the degree of bile acids elevation. The most effective agent for ICP treatment is ursodeoxycholic acid (UDCA). Conclusion. Timely diagnostics of ICP and early UDCA administration, fetus condition control and early delivery at severe ICP cases allows to prevent development of serious complications and to achieve favorable pregnancy outcome.